PENGARUH TEKNOLOGI INFORMASI TERHADAP KINERJA INDIVIDUAL: COMPUTER ANXIETY SEBAGAI VARIABEL MODERATING (STUDI PADA BPR KOTA LAMPUNG) - Lego Waspodo (Universitas Ahmad Dahlan, 2014)
This research is based on the importance of information system technology to the individuals performance, which is moderated with Computer Anxiety. It was used the population Manager of Bank Perkreditan Rakyat (BPR) in Lampung. The infl uence of nformation system technology to the individuals performance was analyzed by using original least square regression, and the infl uence of the moderated variable (Computer Anxiety) to offi cers performance were analyzed by using Moderated Regression Analysis (MRA). The result receives both of the hypothesis.